Time-delay signature suppression in delayed-feedback semiconductor lasers as a paradigm for feedback control in complex physiological networks - Hong, Yanhua; Zhong, Zhuqiang; Shore, K. Alan (Frontiers in Network Physiology, 2024)
Physiological phenomena are often accompanied by time delay effects which may lead to oscillatory and even chaotic dynamics in their behaviors. Analogous dynamics is found in semiconductor lasers subject to delayed optical feedback where the dynamics typically includes a signature of the time delay. In many applications of semiconductor lasers, the suppression of the time delay signature is essential for applications and hence several approaches have been adopted for that purpose. In this paper experimental results are presented wherein photonic filters are utilized in order to suppress time-delay signatures in semiconductor lasers subject to delayed optical feedback effects. Two kinds of semiconductor lasers are used: discrete mode semiconductor lasers and vertical-cavity surfaceemitting lasers (VCSELs). It is shown that, by the use of photonic filters, complete suppression of the time-delay signature may be affected in discrete mode semiconductor lasers but that a remnant of the signature persists for VCSELs.